The Oxidation of Coated SOFC Interconnects in Fuel Side Environments1. Issue 1 (25th November 2015) - Sachitanand, R.; Sattari, M.; Svensson, J.‐E.; Froitzheim, J.
Abstract: This study focuses on examining the effect of PVD coatings on the oxidation performance of interconnects in fuel (anode) side environments. A Fe‐22Cr ferritic steel was coated with (i) Ce 10 nm (ii) La 10 nm and (iii) Co 600 nm. The samples were exposed at 850 °C in Ar‐5% H2 ‐3% H2 O in a tubular furnace over 500 h. Additionally, the effect of a pre‐oxidation step was investigated by exposure in air prior to the simulated fuel gas environment. Chemical analysis on the samples was subsequently performed with SEM/EDX and XRD. It was established that the Ce and La coatings brought about a factor 2–3 reduction ( kp values of 2.16 × 10 −14 ± 3.6 × 10 −15 g 2 cm −4 s −1 for the La 10 nm coated steel compared to 7.72 × 10 −14 ± 5.86 × 10 −15 g 2 cm −4 s −1 for the uncoated steel) in the oxidation rate while the Co coating disintegrated into metallic islands in and on the thermally grown oxide after exposure. Additionally, the La coating resulted in the formation of a continuous perovskite layer by reaction with the thermally grown oxide.